International banking and cross-border effects of regulation: Lessons from Canada - H. Evren Damar; Adi Mordel (Bank of Canada, 2016)
We study how changes in prudential requirements affect cross-border lending of Canadian banks by utilizing an index that aggregates adjustments in key regulatory instruments across jurisdictions. We show that when a destination country tightens local prudential measures, Canadian banks lend more to that jurisdiction, and the effect is particularly significant when capital requirements are tightened and weaker if banks lend mainly via affiliates. Our evidence also suggests that Canadian banks adjust foreign lending in response to domestic regulatory changes. The results confirm the presence of heterogeneous spillover effects of foreign prudential requirements.
Keywords: G01; F34; G21; 330; Financial system regulation and policies; Financial institutions; Financial stability